Urgensi Program Literasi Digital untuk Santri di Asrama Mahasiswa dengan Pendekatan OBE - Jasri, Moh; Holis, Moh Nur; Anabillah, Deni Hairul; Al Fitroh, Moh Farihuddin (Universitas Nurul Jadid, 2024)
Digital literacy is a critical skill in the digital era, particularly for students residing in Islamic boarding school dormitories. This study examines the urgent need for digital literacy programs tailored to students at Universitas Nurul Jadid's dormitories using the Outcome-Based Education (OBE) approach. The research aims to identify students' digital literacy needs, uncover competency gaps, and develop a structured program integrating Islamic values into digital literacy education. A qualitative descriptive case study design was employed, utilizing participant observation, in-depth interviews, and documentation for data collection. Data analysis followed the Miles and Huberman model. Findings highlight significant gaps in students' understanding of digital tools and safe technology usage. The OBE-based program demonstrates potential in improving students' critical thinking, digital ethics, and information literacy while preparing them for the demands of a connected digital world. This study emphasizes the importance of bridging traditional Islamic values with modern digital skills to produce competent and ethical digital users.